A Large Intraperitoneal Residual Volume Hampers Adequate Volumetric Assessment of Osmotic Conductance to Glucose. Issue 5 (September 2018) - Clause, Anne-Lorraine; Keddar, Mehdi; Crott, Ralph; Darius, Tom; Fillee, Catherine; Goffin, Eric; Morelle, Johann
Background: In end-stage renal disease patients treated with peritoneal dialysis (PD), the osmotic conductance to glucose (OCG) represents the intrinsic ability of the membrane to transport water in response to a crystalloid osmotic gradient. A progressive loss of OCG in long-term PD patients indicates the development of fibrosis in the peritoneal interstitium, and helps identify patients at risk for encapsulating peritoneal sclerosis. The double mini-peritoneal equilibration test (PET) has been proposed as a simple method to assess OCG using the difference in initial ultrafiltration rates generated by 2 successive dwells using 1.36% and 3.86% glucose-based, 1-h PET. However, the presence of a large peritoneal residual volume (RV) may potentially interfere with the correct evaluation of drained volumes, limiting the reliability of OCG assessed by the double mini-PET. Methods: We retrospectively reviewed data from 53 peritoneal function tests in 35 consecutive PD patients starting PD at our center between March 2013 and March 2017. The test consisted of a uni-PET (double mini-PET combined with a 3.86%, 4-h PET) performed at PD start, then yearly. In addition to peritoneal solute transport rate and net ultrafiltration, the tests provided information about osmotic water transport (OCG, sodium sieving, and free-water transport) as well as the RV estimated from albumin dilution. Results: Contrary to sodium sieving, net ultrafiltration, and free-water transport, OCG did not correlate with any of the other parameters of osmotic water transport. In multivariate regression analyses, the RV was identified as the only determinant of OCG, while it did not alter the robust association between sodium sieving/free-water transport and their respective determinants. Considering only baseline tests or the whole series of tests, the presence of a large intraperitoneal RV was associated with discrepant values between OCG and sodium sieving, and with an artificial increase in OCG. Conclusions: A large RV leads to significant overestimation of OCG using the double mini-PET, potentially reducing the ability of OCG to identify patients with progressive fibrosis in the peritoneal interstitium. On the other hand, sieving of the dialysate sodium, a biochemical surrogate for OCG, is independent of the RV and may therefore be more reliable. A call for caution is warranted in patients with a large RV to avoid misinterpretation of OCG values derived from the double mini-PET.